2016
DOI: 10.1186/s12872-016-0349-5
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic aetiology, self-reported frailty, and gender with respect to cognitive impairment in chronic heart failure patients

Abstract: BackgroundDecisive information on the parameters involved in cognitive impairment in patients with chronic heart failure is as yet lacking. Our aim was to determine the functional and psychosocial variables related with cognitive impairment using the mini-mental-state examination (MMSE) with age-and education-corrected scores.MethodsA cohort study of chronic heart failure patients included in an integrated multidisciplinary hospital/primary care program. The MMSE (corrected for age and education in the Spanish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 59 publications
(63 reference statements)
2
32
1
Order By: Relevance
“…Elderly women in our sample had lower levels of cognitive function with higher prevalence of cognitive impairment than men. Our result confirmed that women with HF had lower cognitive function when compared to men [13,34]. However, it was not in concordance with previous studies which showed that women had an advantage over men in verbal memory tasks [35].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Elderly women in our sample had lower levels of cognitive function with higher prevalence of cognitive impairment than men. Our result confirmed that women with HF had lower cognitive function when compared to men [13,34]. However, it was not in concordance with previous studies which showed that women had an advantage over men in verbal memory tasks [35].…”
Section: Discussionsupporting
confidence: 57%
“…Lower educational attainment and personal income may influence increased risk of cognitive impairment because lower socio-economic status is associated with poor nutritional intake, less access to healthcare services, less social activity and less interpersonal communication, all of which can lead to social isolation [18,36]. On the other hand, other studies have noted that men may experience faster verbal memory decline with the earlier onset of CAD and a higher risk for incident mild cognitive impairment [13]. However, even though there was a higher prevalence of CAD among men in this study, cognitive impairment was significantly prevalent among women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological basis of frailty has not been clearly identified yet. It could reflect cumulative results of pathophysiological modifications caused by concurrent chronic conditions [ 8 ], subclinical adaptation of systemic homeostatic mechanisms [ 9 ], metabolic modifications, and behavioral factors [ 5 ]. Some pathways are shared by frailty and mild cognitive impairment/Alzheimer’s disease (AD).…”
Section: Introductionmentioning
confidence: 99%
“…In daily clinical practice, patients are referred for ICD implantation based on multiple clinical parameters, such as frailty and overall prognosis. Severity of HF is associated with age, co-morbidities, and lower social status, 21,22 and it is possible that patients with severe HF are more often refused for prophylactic ICD therapy. This may influence the comparison of the benefit of ICD therapy in asymptomatic and symptomatic HF patients.…”
Section: Discussionmentioning
confidence: 99%